Teknik Pemeriksaan Parasit Myxobolus sp. pada Ikan Hias Air Tawar di Balai Karantina Ikan Pengendalian Mutu dan Keamanan Hasil Perikanan Surabaya I - Khoirun Nisa; Subhi Indriyani; Ayuda Dyah Nurekawati; Muhammad Aidil Fitri; Hapsari Kenconojati; Retno Septiwulan; Kale Khairi Putik Nurikhwani; Fara Amalia Dewi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The increase in ornamental fish farming in Indonesia has increased significantly during the 2017-2019 period. This improvement process is certainly faced with various challenges such as disease, which is caused by ectoparasites, one of which is Myxobolus sp. This parasite can infect the skin and gills of fish, causing significant financial losses. This study aims to determine the prevalence and intensity of Myxobolus sp parasites in freshwater ornamental fish at the Surabaya I Fish Quarantine Center for Quality Control and Safety of Fishery Products (BKIPM), which was conducted on June 19 - August 18, 2023. The tools and materials used include fish samples, distilled water, 70% alcohol, giemsa dye, swallow and tissue, tray, binocular microscope, computer, dissecting set, object glass, cover glass, dropper pipette, ruler, gloves, beaker glass, workbook, method, and stationery. Native and staining methods were used to examine parasites, while prevalence and intensity were calculated using Kabata's (1985) formula. The results showed that comet fish and koi fish were infected with Myxobolus sp in their gills. The intensity of Myxobolus sp infection in koi fish was classified as severe, while in comet fish it was classified as very severe. The prevalence of Myxobolus sp parasites found in koi fish was 2.32% and in comet fish was 4.20%, both categorized as moderate infection.